Prognostic value of impaired hepato‐renal function assessed by the MELD‐XI score in patients undergoing percutaneous mitral valve repair. Issue 4 (17th October 2018) - Spieker, Maximilian; Hellhammer, Katharina; Wiora, Julian; Klose, Simon; Zeus, Tobias; Jung, Christian; Saeed, Diyar; Horn, Patrick; Kelm, Malte; Westenfeld, Ralf
Abstract: Objectives: The objective of this study was to assess the prognostic value of the Model for End‐stage Liver Disease (MELD)‐XI score in patients undergoing PMVR with the MitraClip system. Background: MELD‐XI score, which was originally developed for prognostic assessment in patients with advanced liver disease, has been reported as a predictor of outcome in heart failure patients. Methods: A total of 192 consecutive patients undergoing percutaneous mitral valve repair (PMVR) were included into final analysis. MELD‐XI score was calculated on the day of the procedure and patients were categorized into three groups based on MELD‐XI score and compared with regards to clinical characteristics and outcomes following PMVR. Results: MELD‐XI > 12 was associated with male gender, higher logistic EuroSCORE, reduced left ventricular ejection fraction, enlarged right ventricular end‐diastolic diameter, degree of mitral regurgitation, increased NT‐proBNP serum levels and elevated right atrial pressures. Youden‐Index revealed a cutoff of 16 in the MELD‐XI score as best predictor of one‐year all‐cause mortality. Kaplan–Meier analysis and the log‐rank test confirmed increased one‐year mortality in patients with critically high score above 16 (mortality MELD‐XI score > 16 vs 16–12 vs <12:39% vs 9%. vs 15%; P  = 0.005). Compared to patients with lower MELD‐XI score, these patients exhibited a more than 3‐fold increased one‐year mortality after PMVR. Conclusion: Given the high mortality in patients with a MELD‐XI score > 16, these patients require a high‐risk preoperative assessment and should undergo a careful discussion within the heart team for the best treatment option given the considerable one‐year mortality following PMVR.